Syrian Refugees, Applied Theater, Workshop Facilitation, and Stories. By F. Skeiker. Routledge, 2020, 108 pp. : While They Were Waiting - Garcés-Amaya, Diana P. (Refuge: Canada's Journal on Refugees, 2023)
book review